Evaluación Presupuestaria al Gobierno Autónomo Descentralizado Parroquial Rural de Curtincápac Canton Portovelo Provincia de el Oro, Período 2015 - Medina Alvarado, Silvia Sofía (2017)
During the development of the present work denominated "BUDGET EVALUATION TO THE AUTONOMOUS GOVERNMENT RURAL PARTICLE OF CURTINCÁPAC CANTÓN PORTOVELO PROVINCE OF EL ORO, PERIOD 2015" ,was executed in compliance with the institutional objectives, considering the procedures of evaluation of the regulation issued by the Ministry of Economy and Finance with the purpose of measuring the management of this period. In order to fulfill the objectives of thesis work; It was considered necessary the analysis of the budgetary management by the Parochial Government; Information was collected such as: annual operating plan, budget execution status, initial budget and revenue and expenditure budget cells for the period 2015. A comparison was made between the Annual Operational Plan and the Executed Projects the same reflects That of the ten planned projects were executed five, which complied with 50% of the planned projects. To measure efficiency and effectiveness in the development of activities, the following financial financial indicators were applied in the financial dependence of the entity was 83.38% in 2015; In terms of financial solvency, current revenues are sufficient to cover recurrent expenditure with a result of 1.05 times, income and budgetary expenditure indicators as well as budget 5 reforms were also applied, according to the need to assess compliance between planned And the execution of income and expenditure within the Parish Government. At the end of the thesis work, a report was prepared on the results obtained in the evaluation, a document that will be submitted to the highest authority, which details the conclusions and recommendations that will help the Board's Better decisions, for the good management of the budget of the public sector and thus to be able to improve the management in later activitie